In Search of Dialogicity: A Comparison of Curricular Documents and Classroom Interactions from Finland and Hong Kong - Sami Lehesvuori; Kennedy Kam Ho Chan; Umesh Ramnarain; Jouni Viiri (MDPI AG, 2017)
The prevailing consensus is that science teaching should be more student-centered and guide learners towards more phenomenon-based and authentic problem-solving activities. This approach is reflected in educational policies and recently reformed curricula. However, there is limited research on how these frameworks actually manifest in curricula and how to facilitate student-centered pedagogy. In this study, we examine the student-centered features of the curricula of two countries: Finland and Hong Kong. Student-centeredness in the classroom can be assessed using the principles of dialogicity. Dialogic principles underpin student-centeredness, particularly in teacher-orchestrated whole-class discussions. Dialogic interactions include mutual consideration of different and even diverging views. This study first reviews the dialogic themes in the curricula, then explores the ways in which student-centered approaches can be realized in practice by analyzing the dialogic interactions in two classroom examples. The dialogic themes identified in the curricula are considered in the context of the classroom examples. As science classroom interactions are still prevailingly teacher-centered and authoritative, the insights into alternative approaches generated by the examples are discussed. This study prepares the context for further discussion of curricular development, dialogicity and its implications for teaching and teacher education.